Design and Development of Hydrothermal Carbonization Reactor - Calistus Princewill Odeh; Orobosa Kingsley Osasuwa; Augustine Uzodimma Madumere; Sunday Chimezie Anyaora (Journal Majelis Paspama, 2026)
This project presents the design, development, and evaluation of a hydrothermal carbonization (HTC) reactor for the conversion of biomass into carbon-rich hydrochar. The reactor was designed to operate under subcritical water conditions with controlled temperature and voltage inputs. Experimental tests were conducted at three voltage levels (185V, 210V, and 220V) and target operating temperatures of 180°C, 200°C, and 220°C. The results showed that heating rate and energy efficiency were directly influenced by voltage level. At higher voltages, the reactor attained the set temperatures in shorter times, with 220V achieving 220°C in 37 minutes compared to 44 minutes at 185V. The evaluation confirmed a linear correlation between temperature and time for all test conditions. The developed reactor demonstrates the potential for efficient thermal processing of wet biomass without prior drying, offering a sustainable pathway for waste-to-energy conversion. The study provides a foundation for further optimization of HTC reactor designs to enhance efficiency and scalability for industrial applications.